Clients' perceptions and satisfaction with HIV counselling and testing: A cross-sectional study in 56 HCT sites in South Africa - Gladys Matseke; Karl Peltzer; Neo Mohlabane (AOSIS, 2016)
Background: Client satisfaction serves as a predictor for acceptance of HIV counselling and testing (HCT) services. Therefore, the study of clients' perception and satisfaction may offer insights on how to improve HCT programmes. Aim and setting: The aim of this study was to assess clients' satisfaction with HCT as well as describe perceived barriers to and facilitators of HIV testing by HCT clients in South Africa. Methods: A cross-sectional survey was conducted through interviews with 498 clients purposefully selected at the end of an HCT visit at 56 HCT sites throughout the country. Results: All the 498 study participants had tested for HIV with 98.8% receiving their results. Most (88.2%) reported testing for HIV before. The vast majority (75.5%) of clients reported that they had decided to be tested for HIV by themselves. High levels of satisfaction with HCT service (89.8%), low levels (27.7%) of difficulty in making the decision to have an HIV test and high levels of perceived confidentiality (94.6%) of the HIV test results were reported in this study. The most cited perceived barrier to HIV testing was lack of awareness about the HCT service (98%), while staff attitudes (37%), confidentiality (29.6%) and privacy (23.6%) were perceived facilitators. In multivariate logistic regression, staff attitude was significantly associated with client satisfaction (p < 0.05). Conclusion: High levels of client satisfaction with HCT services were observed. Various barriers to and facilitators of - including staff attitude - HCT were identified which can help guide the improvement of HCT services in South Africa.